Sensitivity and specificity of photopic negative response of focal electoretinogram to detect glaucomatous eyes. Issue 2 (18th August 2009) - Machida, S; Tamada, K; Oikawa, T; Yokoyama, D; Kaneko, M; Kurosaka, D
Abstract : Aims: To determine the sensitivity and specificity of the photopic negative response (PhNR) of the focal electroretinograms (ERG; focal PhNR) to detect glaucomatous eyes with different degrees of visual field defects. Methods: One-hundred and fourteen eyes of 114 patients with open angle glaucoma and 42 eyes of 42 normal controls were studied. The focal ERGs were elicited by a 15° stimulus spot centred on the macula, and on the supero-temporal and on the infero-temporal areas of the macula. The receiver operating characteristic curves were determined to obtain optimal cut-off values. Eyes were classified as being glaucomatous when their focal PhNRs were less than the cut-off values in either retinal area (combined criterion). Results: The focal PhNR amplitudes were significantly reduced with an advance in the stage of glaucoma. In early glaucoma, the sensitivities of the PhNR measured for each retinal area ranged from 58.1% to 80.7%. The sensitivities were significantly increased to 90.6% and 96.9% for the focal PhNR amplitude and the focal PhNR/b-wave amplitude ratio, respectively, when the combined criterion was employed. The specificity was >90%. Conclusions: Focal PhNRs have diagnostic ability in detecting early glaucoma with high sensitivity and specificity, especially when the combined criterion is used.